An Interaction Effort Score for Web Pages - Gardey, Juan Cruz (2022)
There is a lack of automatic evaluation models to measure the user experience (UX) of online systems, especially in relation to the user interaction. In this paper we propose the interaction effort score as a factor that contributes to the measure of the UX of a web page. The interaction effort is automatically computed as an aggregation of the effort on each interactive widget of a page, and for all users that have interacted with them. In turn, the effort on each widget is predicted from different micro-measures computed on the user interaction, by learning from manual UX expert ratings. This paper describes the evaluation of the interaction effort of different web forms, and how it compares to other metrics of usability and user interaction. It also shows possible applications of the interaction effort score in the automatic evaluation of web pages.